Asymmetry of force generation and neuromuscular activity during multi-joint isometric exercise - Seita Kuki; Yu Konishi; Masamichi Okudaira; Takuya Yoshida; Tim Exell; Satoru Tanigawa (Japanese Society of Physical Fitness and Sports Medicine, 2019)
The purposes of the present study were (a) to determine whether a self-reported dominant leg was consistent with a dominant leg of force generation by using the isometric mid-thigh pull (IMTP) tests and (b) identify the features of bilateral IMTP (IMTPBi) and unilateral IMTP (IMTPUni) in terms of detecting strength imbalance of athletes. Fifteen male collegiate athletes performed IMTPUni and IMTPBi. The ground reaction force and surface electromyography were sampled with 1000Hz to assess force generation and neuromuscular activities in the gluteus maximus (Gmax), gluteus medius (Gmed), semitendinosus (ST), biceps femoris (BF), rectus femoris (RF) and vastus lateralis (VL) during IMTP. Legs were separated into dominant and non-dominant leg categories in accordance with two types of definitions including self-reported dominance of kicking leg and dominance of force generation in IMTP. In force generation and neuromuscular activity of IMTPBi and IMTPUni, there was no significant difference between self-reported dominant and non-dominant leg. However, results for a self-reported dominant leg were not consistent with results for dominant leg determined by force generation. In addition, the dominant leg of force generation exerted significantly larger PF than non-dominant leg, and the magnitude of asymmetry in IMTPBi was significantly larger than that of IMTPUni. Moreover, in IMTPBi, the neuromuscular activity of the VL of the dominant leg of force generation was significantly larger than that of the non-dominant leg. Therefore, it was suggested the necessity to distinguish the two types of IMTP tests because of the possibility that the strength imbalances detected by IMTPBi and IMTPUni would have different connotations.